2021
DOI: 10.1111/jcmm.17091
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5‐mediated m6A modification of lncRNA KCNQ1OT1 triggers the development of LSCC via upregulation of HOXA9

Abstract: Laryngeal squamous cell carcinoma (LSCC) is the most common pathological subtype (>95%) of laryngeal carcinoma. 1,2 The prevalence of LSCC was ranked as 2nd in head and neck squamous cell carcinoma (HNSCC). It is reported that in 2018, there were 177,422 new cases of LSCC and 94,771 deaths of LSCC in the world. 3 Notably, the incidence of LSCC in China is about four times that in the United States, with an estimated death toll of more than 15,000 per year. 4 The 5-year overall survival (OS) rate of patients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…For example, the lncRNA UBA6-AS1 inhibits the decay of UBA6 mRNA by modifying the methylation status of m6A, thus suppressing ovarian cancer cell malignancy [ 16 ]. The m6A demethylase ALKBH5 mediates the modification of the methylation of the lncRNA KCNQ1OT1, thus upregulating the expression of the HOXA9 gene and promoting the development of laryngeal squamous cell carcinoma [ 17 ]. Nevertheless, previous studies have focused primarily on m6A methylation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lncRNA UBA6-AS1 inhibits the decay of UBA6 mRNA by modifying the methylation status of m6A, thus suppressing ovarian cancer cell malignancy [ 16 ]. The m6A demethylase ALKBH5 mediates the modification of the methylation of the lncRNA KCNQ1OT1, thus upregulating the expression of the HOXA9 gene and promoting the development of laryngeal squamous cell carcinoma [ 17 ]. Nevertheless, previous studies have focused primarily on m6A methylation.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous deepening of lncRNA research, there have been more and more studies on lncRNA methylation modification in recent years. Li et al [ 37 ] investigated the role and mechanism of m6A modification of lncRNA KCNQ1 overlapping transcript 1 (KCNQ1OT1) in the progression of laryngeal squamous cell carcinoma (LSCC), suggesting that ALKBH5-mediated m6A modification of KCNQ1OT1 is triggered by the upregulation of HOXA9 LSCC development. Liu et al [ 38 ] identified the differentially expressed lncRNA in gastric cancer and found that the m6A modification of THAP7-AS1 by METTL3 enhanced its expression, and its high expression was associated with positive lymph node metastases and a poor prognosis in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that ALKBH5-mediated m6A demethylation of the lncRNA RMRP plays an oncogenic role in lung adenocarcinoma [ 25 ]. It has also been shown that ALKBH5-mediated m6A modification of lncRNA KCNQ1OT1 regulates the development of LSCC [ 63 ], and that ALKBH5-mediated m6A modification of PVT1 promotes the progression of OS [ 51 ]. The two studies also showed YTHDF2 could recognize m6A-modified sites of lncRNA KCNQ1OT1 or PVT1 and regulate their stability [ 51 , 63 ], but whether ALKBH5 regulates the stability of PVT1 via YTHDF2 in lung cancer cells remains to be examined further.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that ALKBH5-mediated m6A modification of lncRNA KCNQ1OT1 regulates the development of LSCC [ 63 ], and that ALKBH5-mediated m6A modification of PVT1 promotes the progression of OS [ 51 ]. The two studies also showed YTHDF2 could recognize m6A-modified sites of lncRNA KCNQ1OT1 or PVT1 and regulate their stability [ 51 , 63 ], but whether ALKBH5 regulates the stability of PVT1 via YTHDF2 in lung cancer cells remains to be examined further. Further, we also showed that a serious tumor-related genes could be regulated by ALKBH5-PVT1 axis, but the functional evidence is still lacking.…”
Section: Discussionmentioning
confidence: 99%